Contact dynamics of cytoadhering plasmodium falciparum-infected erythrocytes in flow - Scholz, Katharina; Papagrigorakes, Marianne; Lettermann, Leon; Pennarola, Federica; Patra, Pintu; Dasanna, Anil Kumar; Sanchez, Cecilia P.; Kehrer, Jessica; Cavalcanti-Adam, Elisabetta A.; Schwarz, Ulrich S.; Tanaka, Motomu; Lanzer, Michael (ACS infectious diseases, 2025)
The virulence of the human malaria parasite Plasmodium falciparum is linked to the altered mechanical and adhesive properties of infected erythrocytes, which adhere to the microvascular endothelium to evade splenic clearance. The underlying biophysical mechanisms remain incompletely understood, particularly regarding the contact area and bond landscape, due in part to the rapid and transient nature of these interactions. In this study, we investigated the dynamic adhesion behavior of P. falciparum-infected erythrocytes on surfaces functionalized with intercellular adhesion molecule 1 (ICAM-1), cluster of differentiation 36 (CD36), or a combination of both. To this end, we employed DNA-based molecular force sensors, high-speed reflection interference contrast microscopy, and computer simulations. Our results show that trophozoite-stage infected erythrocytes, which maintain a discoidal shape, exhibit complex motion behaviors across all substrates, including flipping over the long axis and flipping combined with lateral sliding, with or without pinning, producing patchy adhesion footprints. In contrast, schizont-stage parasites display a more uniform rolling motion, occasionally accompanied by sliding or pinning, consistent with their spherical morphology and stiffened membrane. We further observed that the incidence of sliding increased on CD36-containing surfaces for both developmental stages. Notably, some adhesion footprints extended across distances comparable to the length of an endothelial cell. Together, these findings provide new insights into the complex biophysical adaptations of P. falciparum-infected erythrocytes, offering a more detailed understanding of the mechanisms driving cytoadhesion and its potential impact on microvasculature pathology.
Gesehen am 15.12.2025